Binding factors between agreements of programmation in the regions of Los Lagos, Los Rios and Araucanía, and a tool for regional planning (Revista LIDER, 2020)
This study describes the binding factors between the programming agreements in force in the regions of Los Lagos, Los Ríos and La Araucanía, as an instrument for spatial planning. Besides, it systematizes the background on current ways of developing and implementing these agreements, and finally identifies the strengths and weaknesses of the Chilean model of programming convention for other international models. These analyses were based on the lifting of secondary information, indepth interviews to reporting key informants of the regional administrative level and participant observation of the own researcher involved in the matter, which made it possible to determine the main critical factors of integration into existing programming conventions and a territorial Plan to recommend that they act as governance agreements.